OXIDATIVE STRESS AND LEVEL OF IRON INDICES IN CORONARY HEART DISEASE PATIENTS - Ahmad, Muhammad; Khan, Mudassir Ahmad; Khan, Abdus Sattar (Journal of Ayub Medical College Abbottabad, 2009)
Objective: Oxidative stress is characterized by an increased concentration of oxygen free radicals which can cause a critical, or even an irreversible, cell injury. The study was designed to determine and compare the levels of oxidative stress and iron indices in Coronary Heart Disease and healthy individuals. Material and Methods: Blood malondialdehyde, iron, total iron-binding capacity, transferrin saturation and ferretin levels were determined in 140 Coronary Heart Disease and 100 healthy subjects. Results: Values of blood malondialdehyde, iron, transferrin saturation and ferretin were observed to be significantly increased with exception of total iron-binding capacity, which was significantly decreased (pï€¼0.005) in Coronary Heart Disease patients when compared with normal healthy controls. Conclusion: Elevated serum malondialdehyde, iron concentration and body iron stores in patients reveal a possible role of iron indices in the development of coronary atherosclerosis. Therefore, it is suggested by this study that levels of malondialdehyde and biochemical markers of body iron stores can be used as an early investigative tool for assessing the oxidative stress in coronary heart disease. Keywords: Coronary Heart Disease, Oxidative Stress, Malondialdehyde, Iron, Total iron-binding capacity, Transferrin Saturation, Ferritin